Peningkatan Pengetahuan Tata Laksana Trauma Gigi Sulung pada Anggota Komunitas BCApril21: Peningkatan Pengetahuan Tata Laksana Trauma Gigi Sulung pada Anggota Komunitas BCApril21 - Hayuningtyas, Ria Aryani; Laksmiastuti, Sri Ratna; Lestari, Sri; Louisa, Marie; Livia Kurniawan, Florencia (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
ABSTRACT A study reveals a global prevalence of 22,7% of dental trauma affecting primary teeth through a meta-analysis. Among children aged 0-6 years, oral injuries contribute to 18% of total physical injuries. Dental trauma in children has significant consequences on their oral health. Managing dental trauma in children poses challenges for parents and patients. An education and training activities were held to increase the knowledge of mothers in handling primary dentition dental trauma and management of children’s oral health. This event was carried by Faculty of Dentistry Universitas Trisakti staff members on Mei 2023. This education and training activities were given to Birth Club April 2021 community members. After series of this event, the participant seems to have an increase in knowledge which can be seen in the increase of participant correct post-test answer around 8,82%. Support and participation from the community also contribute to the success of education and training activities. With increased parental knowledge, it is hoped that serious dental health issues in children can be prevented, aiding them in growing up with healthy and strong teeth.